Patient safety education in anesthesia: current state and future directions. Issue 6 (December 2021) - Harbell, Monica W.; Methangkool, Emily
Abstract : Purpose of review: Although patient safety is a core component of education in anesthesiology, approaches to implementation of education programs are less well defined. The goal of this review is to describe the current state of education in anesthesia patient safety and the ideal patient safety curriculum. Recent findings: Anesthesiology has been a pioneer in patient safety for decades, with efforts amongst national organizations, such as the American Society of Anesthesiologists and the Anesthesia Patient Safety Foundation to disseminate key standards and guidelines in patient safety. However, few, if any strategies for implementation of a patient safety curriculum in anesthesiology exist. Summary: Patient safety education is crucial to the field of anesthesiology, particularly with the advancement of surgical and anesthesia technologies and increasing complexity of patients and procedures. The ideal patient safety curriculum in anesthesiology consists of simulation, adverse event investigation and analysis, and participation in process improvement. Efforts in education must adapt with changing technology, shifts in the way anesthesia care is delivered, and threats to physician wellness. Future efforts in education should harness emerging platforms, such as social media, podcasts, and wikis.